Memory in T. S. Eliot’s The Waste Land - Phuyal, Komal Prasad (Khwopa Journal, 2023)
The greatest of the issues in modernism emanates from memory in human beings. It is the first condition for people to realize what they have lost in their life, resulting from World War I. Often known as the manifesto of modernism in the West, T. S. Eliot’s 1922 poem The Wasteland deals with the intellectual, social, political, and quotidian issues of the people, basically resulting from memory. The people begin to value the glory of the past as the epitome in contemporary times, meaning that they have been driven out of paradise now. In other words, memory became a tool to rewrite a new Bible in the twentieth century following the trail of John Milton’s The Paradise Lost (1667). The phantoms of negative memories torment the people in the West: for instance, the people set out in search of Christ or metonymically the Holy Grail. Most importantly, the poetic persona is Tiresias who still remembers both his lives. He searches for the images that best represent the experience of living in the Western world shattered at the hand of the destructive forces. The centers of the civilizations have undergone massive destruction and they have remained unable to reconstruct themselves. Both the poet and the poetic persona go through the pages of the books of the Western and Eastern body of knowledge to identify the remedy for the fragmentation or loss of the binding principles of human society. This study aims to explore how memory is treated in modernist literature to examine the presence of history in making sense of the presence. The Eastern myths remind the Western world of the cure to the existing problems of society. In fact, this paper claims that The Wasteland builds its argument in the treatment of memory as the prime factor in the articulation of the central vision about the West in general and modernism in particular.